Biportal endoscopic spine surgery for treatment of thoracolumbar intervertebral disc herniation in 13 dogs - Kim, Yongsun; Lim, Ji-Hey; Ryu, Yebin; Choi, Dae Jung (Frontiers in Veterinary Science, 2025)
ObjectiveThis study aimed to describe the technique and evaluate the clinical outcomes of utilizing a biportal endoscopic spine surgery (BESS) for the treatment of thoracolumbar intervertebral disc herniation (IVDH) in dogs.MethodsThirteen client-owned dogs diagnosed with single level thoracolumbar IVDH using magnetic resonance imaging were included. A mini-hemilaminectomy was performed using the BESS system. Briefly, the dogs were positioned in sternal recumbency and two portal skin entry points were confirmed under fluoroscopic guidance. The endoscopic portal provided continuous irrigation and visualization, while the instrumental portal allowed for instrument manipulation and disc removal. Pre- and postoperative neurologic status, operation time, perioperative complications were recorded and analyzed.ResultsThe dogs ranged in age from 4 to 11 years (median 7.5 years) and weighed ranging from 5.0 to 9.1 kg (median 7.4 kg). Clinical presentations ranged from ambulatory paraparesis to non-ambulatory paraparesis. The BESS approach enabled effective spinal cord decompression and removal of extruded disc material without intraoperative complications. No cases required conversion to open hemilaminectomy. The average operation time was 53 ± 10.5 min. At 6 weeks postoperatively, all dogs exhibited normal neurological function, and no complications were reported.ConclusionThese clinical findings support that minimally invasive BESS is a safe and feasible technique for treating thoracolumbar IVDH in small-breed dogs. The BESS approach offers an effective surgical alternative for the treatment of thoracolumbar IVDH in canine patients.